Projected climate change effects on suitable habitat for Pseudosuccinea columella and Radix natalensis in uMgungundlovu, South Africa - Mpumelelo Ian Hadebe; Tawanda Manyangadze; Chester Kalinda; Moses John Chimbari (PLoS ONE, 2026)
Introduction Climate change impacts oceanic and atmospheric circulation patterns, precipitation, air and sea surface temperatures leading to altered intermediate host vector distribution, reproduction, and maturation. With temperatures predicted to rise by 1.5°C or more, understanding the influence of environmental characteristics and climatic conditions on distribution of intermediate host vectors, occurrence and habitat suitability is vital in vector borne diseases and their control policies. Hence, the study focused on the predicted changes in habitat suitability of Pseudosuccinea columella and Radix natalensis in uMgungundlovu district under climate change scenarios. Methods Freshwater Pseudosuccinea columella and Radix natalensis were collected from seven localities in uMgungundlovu using stratified random cluster sampling. Snail samples were collected at 45 sites. The sites were selected based on local knowledge and accessibility. The ensemble model assessed climate variability, while Representative Concentration Pathways (RCP) predicted habitat appropriateness for P. columella and R. natalensis . Maps were created using the MaxEnt model, and the model’s performance was assessed using the Area Under the Curve (AUC) of the receiver operating characteristic (ROC) curve. Results Our study indicates that P. columella and R. natalensis under current climatic conditions have suitable habitats in the Mpofana, Impendle, Richmond, and Mkhambathini municipalities within the uMgungundlovu district, but the central and northern regions are considered unsuitable. Furthermore, under the RCP4.5 and RCP8.5 climate scenarios, an estimated 22.31% and 22.57% of areas that are presently suitable are expected to become unsuitable for P. columella in uMgungundlovu, with fragmented areas and unsuitable areas becoming suitable for R. natalensis distribution by 2085. Conclusion Climate change could influence the distribution of fasciola intermediate host snails, potentially shifting the hotspots of fascioliasis transmission. Future studies should take into account shifts in land use, evolving agricultural techniques, and the impact of human activities to ensure effective management strategies.